Para leer a Pío Baroja : una meditación de José Ortega y Gasset (Estudios de Historia de España, 2016)
The purpose of this paper is to reconstruct the criticism of Pio Baroja’s novels made by José Ortega y Gasset. To that end, I have mainly concentrated on the analysis of the essay Pío Baroja: anatomia de una alma dispersa, written in 1912 as one part of some refl ections made to be included in a book (Meditaciones del Quijote, 1914), but unpublished during the past several decades and entirely published for the fi rst time in 1988. After reading this text and other Orteguian essays we arrived at the conclusión that, in spite of admitting the undeniable artistic sensibility of his author, Ortega thinks that barojian novels do not reach the necessary maturity that allow us to consider the Basque writer as a great novelist, because all of them has the same faults that affect their form and their content.
Keywords: Pío Baroja; José Ortega y Gasset; Meditaciones del Quijote (1914); El árbol de la ciencia (1911); Novel